Developing collaborative ecosystem platforms to trigger sustainable “place-based” value creation: a dynamic performance governance approach - Bianchi, Carmine; Grippi, Noemi (International journal of productivity and performance management, 2025)
PurposeThis paper aims to illustrate how service ecosystem governance may provide a suitable ground to pursue holistic resilience to “wicked” socio-economic and ecological problems, for enhancing “place-based” sustainable performance outcomes through an organizational, interorganizational and context setting.Design/methodology/approachThis work suggests the use of “place-based” collaborative ecosystem platforms driven by a dynamic performance governance approach as a setting where facilitated performance dialogue is carried out among networked stakeholders. This fosters a holistic view of performance sustainability where intangibles, inertial, cultural and behavioral factors play a key role in policy analysis.FindingsThe paper illustrates how different research streams framing stakeholder relationships under a business, hybrid organization and public sector perspective converge toward the “service ecosystem” construct, as a common field for sustainable “place-based” value creation. This performance governance perspective frames accountability for achieving sustainable outcomes through interconnected viewpoints, i.e. (1) time (short vs long-term), (2) subject (single organization, “theme-focused” service ecosystem and “place-based” service ecosystem) and (3) field (socio-economic, cultural and ecological).Originality/valueThis work has an interdisciplinary track. It recommends feedback and “stock-and-flow” modeling to enhance framing counterintuitive patterns of behavior of dynamic complex socio-economic, cultural and ecological subsystems within “place-based” collaborative ecosystem platforms. Combining an inside-out with an outside-in view triggers sustainable outcome-based dynamic performance governance through an organizational, interorganizational and context setting.